Application of Asset Management Applications at CV.Uberma Computer - Dwi Ifan Ramadhan; Agung Triayudi; Endah Tri Esti Handayani (Institute of Computer Science (IOCS), 2020)
The purpose of this research is to identify a problem, analyze needs, and also develop a management information system, especially in managing an asset data and also storing asset data on a cv.uberma computer, this system will be developed using the PHP7 programming language and also the Framework. AdminLTE bootstrap with MySqli database, using the waterfall method because using the waterfall method can describe a systematic and sequential approach to developing software and also uses the PIECES Framework method to determine the assessment of an application from respondents, with an application asset management information system This will be a solution in presenting an asset data consisting of building assets, store assets, land assets, product assets, computer component assets and computer equipment assets, using an asset management application.